Strategi Pengelolaan Dana BOS Untuk Mewujudkan Efisiensi dan Efektivitas Keuangan Sekolah - Sufia Shalehah; Viony Dwi Arfa; Ermita, Ermita; Fifin Wildanah (CV. ITTC INDONESIA, 2025)
The management of School Operational Assistance (BOS) funds is a crucial aspect that supports the teaching and learning process in schools. BOS is designed to provide the necessary funds so that schools can meet basic operational needs to effectively and efficiently achieve national education goals. Before determining the financial management strategy for the school, there are certainly several issues that pose challenges in effectively managing BOS funds, among which the common problems include delays in the disbursement of BOS funds to the parties/fields that support learning, BOS funds that are distributed still do not meet the routine educational needs of the school, and the improper targeted use of BOS funds so that education in the school does not improve, as well as the lack of knowledge among stakeholders regarding the mechanisms for utilizing funds provided by the government, resulting in the suboptimal use of BOS funds which is often ineffective and inefficient in an educational institution. This research employs a literature review approach based on previous scholarly journals that focus on efforts to achieve financial efficiency and effectiveness in schools. Through this literature study approach, this research identifies general theories in effective BOS fund management strategies. The analysis results show that there are several effective strategies that can be used in the management of School Operational Assistance (BOS) funds from the government for schools, including: systematic planning of fund usage, improving the quality of teaching staff, increasing access to and quality of educational facilities, purchasing teaching materials and learning resources, developing the curriculum, and encouraging student and parental involvement. The strategy for managing School Operational Assistance (BOS) aims to achieve efficiency and effectiveness in school finances, thereby enhancing the quality of education in Indonesia.